EFEKTIVITAS REKAM MEDIK ELEKTRONIK DI KLINIK KUSUMA MEDICAL CENTER BATUKAJANG KALIMANTAN TIMUR - susanto, agus billy; Yaniawati, E. Poppy; Sukajie, Bambang (LPPM-UNIKI, 2024)
Clinics are health facilities that provide medical services, both basic medical and specialist medical services. The obligations of health clinics are regulated in the Republic of Indonesia Minister of Health Regulation no. 269 ​​of 2008, one of which is maintaining medical records. Electronic-based medical records must be carried out by health service facilities in accordance with government policy as stated in Republic of Indonesia Minister of Health Regulation number 24 of 2022 concerning Medical Records. Electronic Medical Record (EMR) is a computerized health information system that provides records of patient data as a decision support system. Kusuma Medical Center Clinic Batukajang, East Kalimantan has implemented EMR since 2021, but its implementation has never been evaluated. The aim of this study was to analyze the effectiveness of EMR at the Kusuma Medical Center Clinic Batukajang, East Kalimantan. The research method that would be used in this research was mixed methods. Research instruments include questionnaires, interview guidelines and observation sheets. Quantitative data analysis was carried out through assumption testing and path analysis (PATH). The research results showed that the implementation of EMR at the Kusuma Medical Center Clinic Batukajang, East Kalimantan has been effective. EMR filling was complete, accurate, timely and in accordance with the law. The results of the analysis showed that employees perceptions of EMR had a positive and significant effect on employees attitudes towards filling out EMR.